Reflexiones acerca de la alternancia : una comparación entre el modelo de prácticas a través del modelo FCT (Formación en Centros de Trabajo) y el aprendizaje en España - María Jesús Martínez Usarralde (Universidad de La Rioja, 2013)
The article analyzes the value and sense of the concept of `Alternancia´ from the educational point of view, and how this initial idea fits in the context of the configuration of the new Vocational Education system and the rol played by the figure of Apprenticeship. One of the fundamental pieces inside the environment of practical questions is, in fact, the role and responsibilities that the company acquires. This aspect forces us to reconsider the relationship between the company and the school center. All these features confer a new sense to the professional practices. Some predict that it is the touch stone that it differentiates this reform from the previous ones, at the same time that it brings us near to our European neighbours. So, the article seeks to open the debate and calls at least for the reflection of the challenges outlined with regard to the configuration of the professional practices, its impact and the repercussions that all the above-mentioned possess from the main characters of the process of practices.